Pengaruh Preferensi Waktu dan Biaya Pada Pemilihan Moda Penumpang Kelas Ekonomi Jurusan Jember – Surabaya - Hamduwibawa, Rofi Budi; Kuryanto, Totok Dwi; Haqiqi, Riski Agil; Alihudien, Arief (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2023)
The construction of the Probolinggo-Pasuruan toll road has resulted in faster travel times along the Jember-Surabaya route. However, it has been observed that economy buses rarely use the toll road. To determine the likelihood of passengers switching between economy-class train and economy-class bus modes, a study on the selection of economy-seat modes between the cities of Jember and Surabaya is necessary. The study utilized the Stated Preference method for data collection, which involved distributing questionnaires to passengers at stations and terminals. The data collected were analyzed using the binomial difference method. The results of the study reveal that the Economy-Class Train mode is the most preferred mode of transportation. Experimentation on the travel cost attribute (ΔX1) with the value of Uka-Ubu Utility = 6.512 - 0.0887(X1) + 0.292(X2) revealed that 99% of passengers chose the train. On the travel cost attribute (ΔX1) with the value of Uka-Ubu Utility = 0.0205 - 0.0034 X1, 55.2% of passengers chose the train. Meanwhile, on the travel time attribute (ΔX2) with the value of Uka-Ubu Utility = 0.0202 - 0.0034 X2, 52.6% of passengers chose the train.